Pengaruh Interaksi Sosial dan Peran Gender Terhadap Pertimbangan Moral Siswa SMA Negeri 12 Medan - Elisabeth Lindawati Sigiro; Asih Menanti; M. Rajab Lubis (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2020)
The study aims (1) to determine the effect of social interaction on students’ moral judgment; (2) to determine the effect of gender role as woman on students’ moral judgment; (3) to determine the effect of social interaction and gender role as woman on students’ moral judgment. The population of this study are students of class XI SMAN 12 Medan amounted to 344 students. The study sample consisted of 135 students, especially woman who were selected using quantitative research and the proportionate stratified random sampling technique. Collected using the moral judgment scale used is Defining Issues Test (DIT), social interaction scale, gender role as woman scale. Data were analyzed using multiple regression analysis. The results show that (1) there is no significant effect of social interaction on students’ moral judgment which is indicated by the coefficients rx1.y = 0.077 and p = 0.373 0.05, It means there is no effect of social interaction on students’ moral judgment; (2) there is no  significant effect of gender role as woman on students’ moral judgment which is indicated by the coefficients rx2.y = 0.028 and p = 0.746 0.05; (3) there is no significant effect of social interaction and gender role as woman on students’ moral judgment which is indicated by the coefficients rx1.x2.y = 0.087 and p = 0.608 0.05. The percentage of contributions given by social interaction and gender role as woman is 0,8 %. The remaining 99,2 % is influenced by other variables not examined in this study.